Dinâmica de sistemas para avaliação de impactos de excesso de peso no transporte rodoviário de cargas - Ghisolfi, Verônica (2018)
The overweight of vehicles in the road freight transportation is one of the causes of bad conditions of the Brazilian highways, reducing the useful life of the pavement, as well as an increase of the accidents. This is the case of the transportation of ornamental stones from the city of Nova Venécia, in the state of Espírito Santo, carried out by two alternative routes, destined to the Port of Vitória, whose activity is the protagonist of several accidents caused by excess weight. Faced with such a problem, which also affects road infrastructure, the overall objective of this work is to present a simulation model to assess the relationship between policies on overweight in road transport and the costs associated with its negative externalities. The proposed model assesses the impact on the general costs of transportation, pavement maintenance and road accidents, under different policies for the loading of ornamental stone vehicles using the Dynamic Systems method. The results confirm the economy of scale by reducing transport operating costs with the practice of overweight by hauliers. However, as the excess weight increases, the social costs with pavement maintenance and road accidents also increase. Therefore, the best vehicle loading policy depends on the relative importance of the economic and social costs involved.